KORELASI FAKTOR SOSIAL EKONOMI DENGAN PENERIMAAN USAHA PERKEBUNAN KELAPA SAWIT RAKYAT DI DESA NANTI AGUNG, KECAMATAN ILIR TALO, KABUPATEN SELUMA - Ivana, Helvera; Priyono, Basuki Sigit; Reflis, Reflis (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
The study of the correlation between social economy factors and the acceptance level of the smallholder palm plantations is conducted in Nanti Agung Village, Ilir Talo Subdistrict Seluma Regency. The aims of the study are to investigate the accepatance level of the smallholder palm plantations and to investigate the correlation between social economic factors and the acceptance of the citizenry palm plantations. The amount of 71 farmers that have main work in palm plantations area are taken by census. Data are analyzed by chi square (X2). The study show that the acceptance level of smallholder palm farmers is in medium/high enough category. Social-economy factors that obviously correlated toward the acceptance level of the smallholder palm plantations are farmer’s age, formal education, the number of workers, and wide area. The other way, the factors that are not correlated toward the acceptance level of smallholder palm plantation farmers are non formal education, motivation, and experinces in plantations working